Herpes Simplex Virus (HSV) Modulation of Staphylococcus aureus and Candida albicans Initiation of HeLa 299 Cell-Associated Biofilm - Plotkin, Balbina J. (Curr Microbiol, 2016)
Although herpes simplex virus type-1 (HSV-1), and type-2 (HSV-2), Staphylococcus aureus and Candida albicans co-habit the oral and genital mucosa, their interaction is poorly understood. We determined the effect HSV has on bacterial and/or fungal adherence, the initial step in biofilm formation. HeLa229 cells were infected with HSV-1 (KOS) gL86 or HSV-2 (KOS) 333gJ(−) at a multiplicity of infection (MOI) of 50 and 10. S. aureus (ATCC 25923) and/or C. albicans (yeast forms or germ tube forms) were co-incubated for 30 min (37 °C; 5 % CO(2); 5:1 organism: HeLa cell ratio; n = 16) with virus-infected HeLa cells or uninfected HeLa cell controls. Post-incubation, the monolayers were washed (3x; PBS), lysed (RIPA), and the lysate plated onto Fungisel and/or mannitol salts agar for standard colony count. The level of HeLa-associated S. aureus was significantly decreased (P < 0.05) for both HSV-1- and HSV-2-infected cells, as compared to virus-free HeLa cell controls (38 and 59 % of control, respectively). In contrast, HSV-1 and HSV-2 significantly (P < 0.05) enhanced HeLa cell association of C. albicans yeast forms and germ tube approximately two-fold, respectively. The effect of S. aureus on germ tube and yeast form adherence to HSV-1- and HSV-2-infected cells was specific for the Candida phenotype tested. Our study suggests that HSV, while antagonist towards S. aureus adherence enhances Candida adherence. Furthermore, the combination of the three pathogens results in S. aureus adherence that is either unaffected, or partially restored depending on both the herpes viral species and the fungal phenotype present.